Bridging the Gap: Addressing Educator and Caregiver Challenges in Transitioning Students with ASD to Higher Education and TVET - A Scoping Review - Nor, Norfezah Md; Mahzan, Nur Afiqah; Abu Bakar, Ahmad Redhuan; Wan Zamri, Wan Nurfarihin; Muhsain, Siti Nur Fadzilah (Information Management and Business Review, 2024)
Students with Autism Spectrum Disorder (ASD) often struggle with communication and social skills, necessitating significant support from family, caregivers, and educators. In Malaysia, while Special Education Needs (SEN) students are typically integrated into general education during their school years, their presence in tertiary education or TVET remains underrepresented. This scoping review aims to identify and understand the challenges general educators and caregivers face in facilitating the transition of ASD students from higher education to tertiary education and TVET. A comprehensive analysis of literature from Scopus, ProQuest, and Science Direct databases, focusing on studies published between 2013 and 2023, was conducted. The findings reveal mixed experiences, highlighting significant difficulties and areas for improvement. General educators and caregivers report numerous challenges, including inadequate training, insufficient resources, and a lack of tailored support systems, which collectively hinder the smooth transition of ASD students into higher educational settings. It suggests that targeted interventions and increased collaboration between educators and caregivers can lead to more positive outcomes. This study provides original insights into the specific needs and barriers faced by ASD students in Malaysia, offering valuable implications for policymakers, educators, and caregivers to create more inclusive and effective educational transitions. Future research on transitioning students with ASD to higher education and TVET should focus on longitudinal studies to track long-term outcomes, the development and evaluation of targeted intervention programs, and the role of assistive technologies in the transition process.